Academic Services to Support Timely Completion of Studies: Students' Needs, Expectations, and Policy Strategies - Sutarto, Sutarto; Sari, Dewi Purnama; Yanto, Murni (Indonesian Journal of Islamic Education Studies (IJIES), 2024)
This research aims to analyze student needs, expectations, and policy strategies for improving academic services to support the timely completion of studies. The type of research used is qualitative with a case study approach. The research informants were 21 students of the IAIN Curup Postgraduate Islamic Religious Education Doctoral Program and four managers of the IAIN Curup Postgraduate Islamic Religious Education and Doctoral Study Program. Data collection techniques used semi-structured interviews. The validity of the data obtained was checked using source triangulation and analyzed using the Miles and Huberman analysis model, which consists of three stages: data condensation, data presentation, and conclusion. The research results found that students' needs and expectations to support the completion of their studies on time can be grouped into two, namely academic services carried out by lecturers and academic services carried out by education staff. To ensure they complete their studies on time, students need and expect academic services that are professional, precise, and fast. The policy strategy implemented by policymakers to support the completion of studies on time is to improve educational services to student needs and expectations by establishing quality policies.